2017
DOI: 10.1002/cpdd.376
|View full text |Cite
|
Sign up to set email alerts
|

Two Phase 1, Open‐Label, Mass Balance Studies to Determine the Pharmacokinetics of 14C‐Labeled Isavuconazonium Sulfate in Healthy Male Volunteers

Abstract: Isavuconazonium sulfate is the water‐soluble prodrug of the active triazole isavuconazole. Two phase 1 studies were conducted to identify the metabolic profile and mass balance of isavuconazole and BAL8728 (inactive cleavage product). Seven subjects in study 1 (isavuconazole mass balance) received a single oral dose of [cyano‐14C]isavuconazonium sulfate corresponding to 200 mg isavuconazole. Six subjects in study 2 (BAL8728 mass balance) received a single intravenous dose of [pyridinylmethyl‐14C]isavuconazoniu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 15 publications
0
13
0
1
Order By: Relevance
“…For the studies with radiolabeled isavuconazonium sulfate, we could not determine the contribution of the by-products of isavuconazole metabolism to the radioactivity in any tissues. Indeed, given that about half of the active isavuconazole moiety in humans is excreted as metabolites in urine ( 31 ), that was likely to be a substantial contributor to the radioactivity detected in kidney and urinary tract tissues. Furthermore, these studies were conducted in healthy animals, and so it is not clear whether the extent of tissue penetration might be substantially affected by inflammation associated with infection.…”
Section: Discussionmentioning
confidence: 99%
“…For the studies with radiolabeled isavuconazonium sulfate, we could not determine the contribution of the by-products of isavuconazole metabolism to the radioactivity in any tissues. Indeed, given that about half of the active isavuconazole moiety in humans is excreted as metabolites in urine ( 31 ), that was likely to be a substantial contributor to the radioactivity detected in kidney and urinary tract tissues. Furthermore, these studies were conducted in healthy animals, and so it is not clear whether the extent of tissue penetration might be substantially affected by inflammation associated with infection.…”
Section: Discussionmentioning
confidence: 99%
“…Predictions of the impact of mucositis were carried out for isavuconazole, broad spectrum antifungal agent, BCS class I (highly soluble and permeable). The drug displays a low intravenous clearance and is mainly metabolised by CYP3A4, predicting an FG of approximately 0.93 (Townsend et al, 2018, Falci and Pasqualotto, 2013, Schmitt-Hoffmann et al, 2006. Kovanda, and co-workers (Kovanda et al, 2017), reported a statistically insignificant reduction in oral AUC (ratio of 0.92) and oral bioavailability (ratio of 0.88) ( Figure 7A and 7B).…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…(Yang et al, 2007, Gertz et al, 2010. For isovuconazole, CLuint was back-calculated from intravenous clearance assuming CYP3A4 metabolism only (Townsend et al, 2018). FG values in gut disease were then predicted using the Qgut model (See Supplementary Material S4 for more details) and compared to observed pharmacokinetic parameters, AUC and Cmax (maximum concentration).…”
Section: Simulation Study 2: Disease Modellingmentioning
confidence: 99%
“…266,270 Mucositis may not rule out oral ISZ use. 268,278 Unlike those of VRZ and PSZ, the IV formulation of ISZ contains no cyclodextrin, as it is water-soluble, and the associated risk of nephrotoxicity is, therefore, very low. 279 ISZ is contraindicated in patients with familial short-QT syndrome.…”
Section: Isz Placementioning
confidence: 99%